Development of Economic Analysis Program Via Matlab’s App Designer - Zaini, Muhammad Nur Izzat; Asmawi, Rosli; Noranai, Zamri (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Economic analysis is a critical part of any business's development process, and it is one of the most important tasks that engineers and scientists have to undertake. In this project, the focus is on developing an accessible and user-friendly economic analysis program using MATLAB and App Designer. The scope of the study includes to using MATLAB software as a database for the economic analysis program, focus on develop program for Return of Investment (ROI) and Net Present Value (NPV) methods and using student version of MATLAB because of cost-free availability. Study of MATLAB App Designer and economic analysis is crucial before proceed to develop the program. Result of the develop program has been validated by make a comparison between manual calculations and the program-generated results, both showing 100% similarity. The successful user friendly economic analysis program managed to develop. This program not only simplifies but also accelerates the process of economic analysis calculations, contributing to a more efficient and accessible approach in financial assessments.